The BRICs superpower challenge foreign and security policy analysis - Chun, Kwang Ho (Ashgate Pub., 2013)
In line with neo-realist approaches, this book argues that in a unipolar world competitors will rise to challenge the global hegemon. As the power profiles of the BRICs rise and they gain greater control of geo-global politics.